Pengembangan Komunitas Islam Berbasis Pemberdayaan: Strategi, Ciri, dan Implementasi Sosial - Mardan Mahmuda (Al-Hikmah: Jurnal Dakwah dan Ilmu Komunikasi, 2025)
Islamic community development is a systematic and sustainable process aimed at improving the social, economic, spiritual, and cultural conditions of Muslim communities based on Islamic principles. This article discusses the concept of Islamic community development, its characteristics, development strategies, and practical implementation through a community empowerment approach. Using a qualitative descriptive method with literature study and case analysis, this study analyzes classical and contemporary theories of community development and compares them with Western development theories. The findings show that Islamic community development emphasizes faith (aqidah), worship (ibadah), morality (akhlaq), and social justice, implemented through staged strategies such as takwin (formation), tanzim (organization), and taudi’ (independence). A case study on mosque-based empowerment of orphans demonstrates that Islamic community development can function as an effective model for social transformation. This article concludes that Islamic community development grounded in empowerment and participatory approaches contributes significantly to social welfare and community self-reliance.